2016
DOI: 10.1590/1519-6984.22814
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visitor number and spice provisioning in pacing expression by jaguars evaluated through a case study

Abstract: Captive animals exhibit stereotypic pacing in response to multiple causes, including the inability to escape from human contact. Environmental enrichment techniques can minimize pacing expression. By using an individual-based approach, we addressed whether the amount of time two males and a female jaguar (Panthera onca) devote to pacing varied with the number of visitors and tested the effectiveness of cinnamon and black pepper in reducing pacing. The amount of time that all jaguars engaged in pacing increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Moreover, the results support the hypothesis that the environmental enrichments improved the conditions of the four jaguars, regardless the individual variation of response, as indicated by behavioral changes expressed by all tested jaguars, like a reduction in 'inactivity' and an increase in activity-related behaviors. Considering that there are, to our knowledge, only a few peer-reviewed publications in this area for jaguars in zoos (Charlton 1998, Skibiel et al 2007, Castillo-Guevara et al 2012, Vidal et al 2016, and that a systematic assessment of the environmental enrichment effects is the exception (Mellen & MacPhee 2001), the study reported here also adds to this literature. The jaguars expressed some responses that were common for the four tested individuals.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Moreover, the results support the hypothesis that the environmental enrichments improved the conditions of the four jaguars, regardless the individual variation of response, as indicated by behavioral changes expressed by all tested jaguars, like a reduction in 'inactivity' and an increase in activity-related behaviors. Considering that there are, to our knowledge, only a few peer-reviewed publications in this area for jaguars in zoos (Charlton 1998, Skibiel et al 2007, Castillo-Guevara et al 2012, Vidal et al 2016, and that a systematic assessment of the environmental enrichment effects is the exception (Mellen & MacPhee 2001), the study reported here also adds to this literature. The jaguars expressed some responses that were common for the four tested individuals.…”
Section: Discussionmentioning
confidence: 86%
“…This may indicate behavioral plasticity or differences related to the different physiological/environmental conditions of the jaguars. In fact, Sellinger & Ha (2005) demonstrated different responses between two captive jaguars exposed to public visitation and also Vidal et al (2016) found individual differences of three jaguars exposed to spice environmental enrichment. Moreover, these findings agree with studies evaluating environmental enrichment effects in other wild cat species, which found significant individual variability of response (Bond & Lindburg 1990, McPhee 2002, Van Metter et al 2008.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Olfactory enrichment is a common approach for addressing stereotypic behavior in captivity animals. Success has been found in olfactory stimulation via the introduction of novel scents (Resende et al, 2011;Vidal et al, 2016;Antonenko, Medvedeva, Panchuk, 2017;Antonenko, Ulitina, Pysarev, 2018). The purpose of the investigation is to establish special aspects of the behavior of the Amur Tiger (Panthera tigris altaica, Linnaeus, 1758) and sensory enrichment with cinnamon oil (Cinnamomum zeylanicum, Blume).…”
Section: Introductionmentioning
confidence: 99%